O paciente portador de Enterococcus resistente a vancomicina em um hospital público de Belo Horizonte: aspectos demográficos, epidemiológicos e microbiológicos - Ledna Bettcher (2008)
This is a descriptive, epidemiologic, retrospective study, with a quantitative approach, which was made in a public hospital in Belo Horizonte. This institution belongs to a chain of hospitals from Fundação Hospitalar of Minas Gerais FHEMIG, which is a reference concerning the treatment of trauma victims. The objective of the study is to define the profile of patients who are infected by resistant to vancomycin Enterococcus (VRE), describing demographic variables, the existence of risk factors, the isolated VRE microbiologic characteristics and the outcome (death rate, the hospital discharging or these patients´ transference). The information was collected from medical records, vigilance forms (standardized by the Hospital Infection Control of the institution) and laboratory results, from May, 2005 to October, 2007. Age,sex, unit and time of hospitalization, basis illness, the use of antimicrobial and drugs to reduce gastric acidity, the existence of open wound, invasive procedures, surgeries, hospital infections, isolated species, Enterococcus sensibility profile and evolution were surveyed. After being collected, the information was registered and processed in a data basis, the Statistical Package for Social Sciences (SPSS) software, 13.0 version, 2004. To analyse all the information, the descriptive statistics was used, by frequency distribution, central trend and variability. One hundred and twenty-two patients took part in the study. The number of colonized patients was five times higher than the one of infected patients, and the E.faecalis was the most prevalent species (59%).We have observed the predominancy of male patients (83.6%) and traumatized ones (80%). The cranioencephalic traumatism was the most frequent one, 50% (61) of the cases, and was followed by abdominal and thoracic, both with the same frequency (17,2%). The average age of the patients was 43 years old and only 8,2% (10) were transferred from other institutions. From 122 patients, 39,3% have been hospitalized in Intensive Treatment Units (UTI) with an average permanence of 30 days. We noticed that 77,9% had had open wounds, 95,9% had used drugs to reduce gastric acidity, 97,5 % had had invasive procedures, 65,6% had undergone surgeries and 88,5% had had hospital infections. The use of antimicrobial was noticed in most patients and 62,3% had used vancomycin, 50,8% cephalosporin of fourth generation, 45,9%cephalosporin of third generation and 40,2% quinolones. The most frequent species were E. faecalis (76) and E. faecium (39), isolated mainly from feces (71,12%) and urine (11,7%). From VRE infections, 63,6% caused by E.faecalis and 31,8% by E. faecium, the urine tractus was the most common situs (72,8%). We realized that 93,0% of E.faecalis were sensitive to ampicilin and ampicilin-sulbactam, but of the E.faecium, only 10,0% were sensitive to ampicilin and 6% sensitive to ampicilin-sulbactam. Among the patients who died (62%), the association with VRE was low (6,5%) and it was most related to theseriousness of the basis illness and infection than to any other microorganism (79%). Facing these results, we can conclude VRE more often colonizes more serious patients, with longer UTI hospitalization and those who have used more than three antimicrobial and have undergone invasive procedures. The frequency of patients with VRE who depend on intensive nurse care shows the importance of this professional, concerning the control and prevention of VRE in the institution.